Supply chain configuration conundrum: how does the pharmaceutical industry mitigate disturbance factors? - Huq, Fahian Anisul/FAH; Pawar, Kulwant S.; Rogers, Helen (Taylor & Francis, 2016)
How a supply chain (SC) is configured can have a significant impact on the performance of global firms. More specifically, disturbance factors (i.e. those factors associated with uncertainty and risk) are increasingly important considerations. This paper focuses on endogenous, exogenous and environment-related SC disturbance factors and their relative importance when configuring global SCs. Three alternative scenarios of SC configurations for European-based pharmaceutical firms are identified - insource nearshore, outsource nearshore and outsource offshore. Through a multi-phase, mixed-method approach we find that the top five disturbance factors managers should be aware of while configuring their SCs are quality defects, unforeseen and random interruptions in manufacturing processes, order processing difficulties, untimely delivery of products, and a mismatch between market demand and supplier responsiveness. This study is able to provide insights into the impact of disturbance factors on the SC configuration strategy for Big Pharmas. We show that SC disturbances influenced the decision to bring production back home (reshoring) or to a closer location (near-shoring). To mitigate the effects of disturbances many Big Pharmas recalibrated their SC configurations by insourcing core products, outsourcing non-core products offshore and developing offshore insourcing capabilities through ‘captives’.